2007
DOI: 10.1088/0022-3727/40/13/011
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional transmission electron microscopy observations on the Berkovich indentation-induced deformation microstructures in GaN thin films

Abstract: Nanoindentation-induced mechanical deformation in GaN thin films prepared by metal-organic chemical-vapour deposition was investigated using the Berkovich diamond tip in combination with the cross-sectional transmission electron microscopy (XTEM). By using focused ion beam milling to accurately position the cross-section of the indented region, the XTEM results demonstrate that the major plastic deformation was taking place through the propagation of dislocations. The present observations are in support of att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…3(b) and (c)). We note that these features are also in contrast to that observed in GaN [29,30] and Al 0.16 Ga 0.84 N films [5], albeit similar Berkovich indenter tip was applied and crystal structure is the same wurzite structure.…”
Section: Resultsmentioning
confidence: 51%
“…3(b) and (c)). We note that these features are also in contrast to that observed in GaN [29,30] and Al 0.16 Ga 0.84 N films [5], albeit similar Berkovich indenter tip was applied and crystal structure is the same wurzite structure.…”
Section: Resultsmentioning
confidence: 51%
“…It clearly shows that multiple pop-ins (discontinuities) in load-displacement curve occur during loading and reflects the process of plastic deformation in the material. The phenomena are usually attributed to dislocation nucleation and propagation during loading as have been observed in a wide variety of materials [14,17], or micro-cracking [18] event. This observation is in contrast to that reported in the previous studies of InP [12,19], where only single "pop-in" event was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to milling, the FIB was used to deposit an ∼1 m thick layer of Pt to protect sample surface. The details of FIB produces in preparing XTEM sample can be found elsewhere [14]. The XTEM lamella was examined in a FEI TECNAI G 2 TEM operating at 200 kV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, the nanoindentation technique plays a key role in understanding nanomechanical properties of thin films. Nanoindentation has been proven to be a powerful technique in providing information on mechanical properties (hardness and elastic modulus) of the investigated materials and variation of these properties with the penetration depth based on analysis of the load-displacement curves [10][11][12][13][14][15][16][17][18][19]. The most important advantage of nanoindentation is to obtain, nondestructively, the films properties without being affected by its substrate.…”
Section: Introductionmentioning
confidence: 99%